Influence Character Education for Youth Morality in the Millennial Generation - Rahman, Saipur; Wahab, Wahab (Jurnal Pengabdian Nusantara, 2025)
The millennial era, characterized by rapid access to information through technology and its positive and negative impacts, presents problems for character education in Indonesia. Therefore, character education is essential to overcome these negative impacts, with systematic intervention from the government. Indonesia is still lagging behind neighboring countries in terms of character education, focusing more on academic achievement. Education should not only provide knowledge, but also build character, in line with the national values enshrined in the 1945 Constitution. In the context of globalization, technology can socially isolate people, even though technology facilitates access to information. Teachers, especially those who teach character-centered subjects, must act as role models and facilitators for students who are heavily influenced by information from smartphones. Character encompasses behavior, personality, and the application of good values, so education should be geared towards forming responsible and socially engaged individuals.